THE DIGITAL DILEMMA: OPPORTUNITIES AND THREATS FOR ELT STUDENTS IN THE EVOLVING CLASSROOM - Kencana, Nila; Elviza Diana; Ellya Revolina; Episiasi; Sam Hermansyah (Language and Education Journal, 2025)
This study explores the opportunities and threats of digital tools in English Language Teaching (ELT) from the perspective of university students. Using a mixed-method approach that combined qualitative interviews and quantitative questionnaires, the research identifies both the benefits and challenges of digital learning environments. Findings reveal that approximately 80% of respondents perceived digital tools as beneficial for improving accessibility and motivation, while nearly 60% reported distractions and technical issues as key obstacles. Theoretically, the study draws on constructivist learning theory, which posits that technology supports learner autonomy when accompanied by meaningful interaction. The results highlight the dual nature of digital learning—its ability to enhance engagement while simultaneously creating new barriers to effective communication and focus. This study contributes to the growing discourse on digital pedagogy by offering contextual insights into ELT students’ experiences, providing practical implications for educators and policymakers seeking to optimize digital learning environments in higher education.